Clinico epidemiological investigation of an outbreak of food poisoning in a girl’s hostel of an educational institute - Debnath, J.; Pardal, Maninder Pal Singh; Shetty, Rajesh; Katyal, Amit; Mangala, Vipra; Raikar, Kedar J.; Kumar, Kamlesh; Kumar, Niranjan; Giri, Ganesh (International Journal Of Community Medicine And Public Health, 2026)
Food poisoning results from ingestion of contaminated food or beverages, commonly presenting as gastroenteritis. Prompt epidemiological investigation is essential for source identification and prevention. In February 2025, following a farewell celebration at a girl’s hostel of an educational institution in India, multiple students developed acute gastroenteritis. The event was catered for by an external vendor, and all affected individuals were female students. Objective was to determine the magnitude, source, and causative agent of the outbreak, and to identify contributing environmental and epidemiological factors. A retrospective cohort study was conducted. All symptomatic individuals were included as cases. Data on symptoms, exposure history, and food consumption was collected via interview and medical record review. Attack rate (AR), relative risk (RR), and attributable risk (AR%) were calculated for each food item. Seventeen of 160 students (AR 10.6%) developed symptoms within 8-24 hours post-exposure. Diarrhoea occurred in all cases, vomiting in 66%, abdominal pain in 76.4%, and fever in 11.8%. Gol Gappa (AR=9.95%) and rice (AR=6.79%) were most strongly associated with illness. Based on symptomatology and incubation period, Salmonella typhimurium was the most probable causative agent; microbiological confirmation was not possible due to lack of food samples. A small-scale outbreak of food poisoning was linked to consumption of Gol Gappa and rice, likely contaminated due to improper handling and storage. Strengthened food hygiene practices and timely outbreak investigations are crucial to prevent recurrence.